1988
DOI: 10.1016/s0006-3495(88)83175-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring relative acetylcholine receptor agonist binding by selective proton nuclear magnetic resonance relaxation experiments

Abstract: A method is presented that uses selective proton Nuclear Magnetic Resonance (NMR) relaxation measurements of nicotine in the presence of the acetylcholine receptor to obtain relative binding constants for acetylcholine, carbamylcholine, and muscarine. For receptors from Torpedo californica the results show that (a) the binding constants are in the order acetylcholine greater than nicotine greater than carbamylcholine greater than muscarine; (b) selective NMR measurements provide a rapid and direct method for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…The spectrum of hydroxamic acid I-1 with stromelysin shows a single set of broadened resonances and a slight change in the chemical shifts, indicative of a fast binding equilibrium between enzyme and inhibitor. Another very sensitive indication of ligand binding with the enzyme can be obtained from selective proton-relaxation measurements (Tisel) (22). Relaxation time measurements (Tisel) for inhibitor I-1 in both the free state and complexed to stromelysin are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum of hydroxamic acid I-1 with stromelysin shows a single set of broadened resonances and a slight change in the chemical shifts, indicative of a fast binding equilibrium between enzyme and inhibitor. Another very sensitive indication of ligand binding with the enzyme can be obtained from selective proton-relaxation measurements (Tisel) (22). Relaxation time measurements (Tisel) for inhibitor I-1 in both the free state and complexed to stromelysin are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The additional NMR peaks in this spectrum arise from the lipid (asolectin) in the vesicles and from mobile amino acid side chains on the protein. [The amount of asolectin was minimized by eluting the purified receptors from the affinity column without asolectin in the elution buffer (8).] The corresponding two-dimensional NOE spectrum of AcCho binding to the AcChoR is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The receptor was purified from the electroplax organs of T. californica as described (8). We have shown that under the conditions used in this study, AcCho binds to the AcChoR and that selective proton relaxation measurements are very sensitive to this binding.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…One of the first methodologies for the use of selective spin-lattice relaxation times on the binding of ligands to biomolecular targets was the study of agonist binding to the acetylcholine receptor of Torpedo californica [61]. In that work, considering that the concentration of the target in relation to the ligand ([L]>>[T]), it was used the equation 1/T 1obs -1/T 1free = f/(T 1 S bound +t bound ), where f is the fraction of the bound ligand and t bound is the lifetime of the ligand-target complex [62].…”
Section: Equationmentioning
confidence: 99%